1991
DOI: 10.2307/1941810
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fluxes in Plant‐Soil Systems at Elevated Atmospheric CO2 Levels

Abstract: The flow of carbon from photosynthesizing tissues of higher plants, through the roots and into the soil is one of the key processes in terrestrial ecosystems. An increased level of CO in the atmosphere will likely result in an increased input of organic carbon into the soil due to the expected increase in primary production. Whether this will lead to accumulation of greater amounts of organic carbon in soil depends on the flow of carbon through the plant into the soil and its subsequent transformation in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
1
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(149 citation statements)
references
References 30 publications
6
141
1
1
Order By: Relevance
“…1) showed under CO 2 enrichment a consistent increase in the most probable numbers of heterotrophs inhabiting rhizospheric soil surrounding L. perenne roots. This result is explained by an increased amount of CO 2 -induced rhizodeposition [47,52,66]. Qualitative changes in the composition of rhizodeposition may also be an explanation, but this feature is not well documented.…”
Section: Impact Of Elevated Co 2 On Heterotrophic Bacteria In the Rhimentioning
confidence: 98%
See 2 more Smart Citations
“…1) showed under CO 2 enrichment a consistent increase in the most probable numbers of heterotrophs inhabiting rhizospheric soil surrounding L. perenne roots. This result is explained by an increased amount of CO 2 -induced rhizodeposition [47,52,66]. Qualitative changes in the composition of rhizodeposition may also be an explanation, but this feature is not well documented.…”
Section: Impact Of Elevated Co 2 On Heterotrophic Bacteria In the Rhimentioning
confidence: 98%
“…Nevertheless, the major influence of a doubling of CO 2 atmospheric concentration on soil microbial communities is indirect because CO 2 concentration in soil is greater than 0.1 kPa [66], whereas the current atmospheric content is 0.035 kPa. Consequently, the main influence is thought to occur by the intermediation of the plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a large proportion of root exudates is used by diazotrophs in the rhizosphere, the assimilation efficiency of root exudates will be much lower than if it is being used by non-nitrogen-fixing microbes. Several studies (Liljeroth et al 1990;Van Veen et al 1991) have shown that the assimilation efficiency of root-derived materials is higher when more nitrogen fertilizer has been used. It is likely that nitrogen fertilization suppresses diazotrophic activity in the rhizosphere, which contributes to higher assimilation efficiency.…”
Section: Microbial Assimilation Efficiency Of Rhizodepositsmentioning
confidence: 99%
“…Because of the abundant supply of available carbon in the form of exudates, microbial growth in the rhizosphere may be highly limited by mineral nutrients. For example, microbial respiration rate in the young wheat rhizosphere is not stimulated by addition of glucose (Cheng et al 1994), but the assimilation efficiency of root-derived materials is higher when more nitrogen fertilizer has been used (Liljeroth et al 1990;Van Veen et al 1991).…”
Section: Microbial Assimilation Efficiency Of Rhizodepositsmentioning
confidence: 99%